PELATIHAN PEMBUATAN DAN PENGUNAAN ALAT PERAGA ‘MONIKA’ DI SD NEGERI NGULAKAN - Novy Trisnani (Jurnal Terapan Abdimas, 2020)
Abstract. Training in the manufacture and use of teaching aids is a form of activity in an effort to improve the quality of teachers to be able to prepare, manage and implement the learning process in accordance with the development of learning innovations. Community Service Activities (PPM) aims to add insight, knowledge, and skills of service participants in understanding how to make and use the 'monika' props. The subjects of this study were classroom teachers and mathematics teachers at SD Negeri Ngulakan. The method of carrying out PPM activities includes presentation of material, training in making media / props, training on the use of props, and evaluation. From the results of the evaluation of PPM activities it can be concluded: 1) participants of service in SD Negeri Ngulakan can make and use 'monika' props 2) useful and meaningful training activities for all service participants, 3) in the practice process of making and using props, service participants did not experience significant difficulties, and 3) from the training activities, the devoted participants gained additional references and experience in choosing and implementing mathematical learning innovations. Abstrak. Pelatihan pembuatan dan penggunaan alat peraga merupakan salah satu bentuk kegiatan dam upaya meningkatkan mutu guru agar mampu mempersiapkan, mengelola, dan mengimplementasikan proses pembelajaran sesuai dengan perkembangan inovasi pembelajaran. Kegiatan Pengabdian pada Masyarakat (PPM) ini bertujuan untuk menambah wawasan, pengetahuan, dan keterampilan peserta pengabdian dalam memahami cara pembuatan dan penggunaan alat peraga ‘monika’. Subjek penelitian ini adalah guru kelas dan guru pelajaran matematika di SD Negeri Ngulakan. Metode pelaksanaan kegiatan PPM meliputi pemaparan materi, pelatihan pembuatan media/alat peraga, pelatihan penggunaan alat peraga, dan evaluasi. Dari hasil evaluasi kegiatan PPM dapat disimpulkan: 1) peserta pengabdian di SD Negeri Ngulakan dapat membuat dan menggunakan alat peraga ‘monika’ 2) kegiatan pelatihan berdayaguna dan bermakna bagi seluruh peserta pengabdian, 3) dalam proses praktek pembuatan dan penggunaan alat peraga, para peserta pengabdian tidak mengalami kesulitan yang berarti, dan 3) dari kegiatan pelatihan, peserta pengabdian memperoleh tambahan referensi dan pengalaman dalam memilih dan menerapkan inovasi pembelajaran matematika.